8.4-Hydroxy-2-nonenal, Induced Nitric Oxide Synthase Status in Hypertension with Kidney Disease Patients (Iraqi Journal of Medical Sciences, 2019)
Background:The oxidative stress is one of the main reasons for cardiovascular diseases and also one of results of these diseases, its development (like kidney disease).Objective:To identify the effect of oxidative stress nitric oxide and reactive oxygen species on cardiovascular diseases.Methods:The study involved 56 subjects comparable in age and sex divided into two groups; 28 hypertensives subjects with kidney disease and 28 apparently healthy subjects as control group. The following analysis was done: 4-Hydroxy-2-nonenal (4HNE), Induced nitric oxide synthase (iNOS) and albumin.Results:There was a significant increase in (4HNE) between patients' group and control group. iNOS was significantly higher in patients as compared to controls while there were no significant differences found in albumin between patient and control group. There is a positive relationship between oxidation results from hypertension and their developments. There is a positive correlation between BMI and disease.Conclusion:Based on this study is important on ideal weight, because obesity considered main factors for heart disease and hardening of the arteries. In addition, the effect of oxidative stress, which leads to high blood pressure and thus chronic kidney disease.Keywords;Chronic kidney disease, hypertension, 4-Hydroxy-2-nonenal (4HNE), Induced nitric oxide synthase (iNOS), albumin, creatinine, reactive oxygen speciesCitation:Hammed AD, Jawad AH, Ali NM. 4-Hydroxy-2-nonenal, induced nitric oxide synthase status in hypertension with kidney disease patients. Iraqi JMS. 2019; 17(2): 146-152. doi: 10.22578/IJMS.17.2.8
Keywords: Chronic kidney disease; hypertension; 4Hydroxy2nonenal 4HNE; Induced nitric oxide synthase iNOS; albumin; creatinine; reactive oxygen species